Promoting Menstrual Health Through Nutritional Education and Peer-Based Interventions in Adolescent Girls: A Scoping Review - Putu Ayu Karisma; Apoina Kartini; Siti Fatimah Pradigdo (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Menstruation, a normal part of puberty, is frequently misinterpreted because of societal stigma and limited access to proper education. Educational settings and peer-based programs are key in enhancing both menstrual and nutritional health, which are vital to supporting the overall well-being of adolescent girls. This Study aims to explore the factors influencing the promotion of menstrual health through nutrition education and peer-based interventions for adolescent girls using a scoping review methodology. Subject and Method: This scoping review was conducted using data obtained from PubMed Central, Science Direct and Google Scholar. The target population includes adolescent girl related to their menstrual health, nutritional education and peer-based intervention. A search was conducted using the keywords “Menstrual health